2004
DOI: 10.1038/sj.bjc.6602211
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between interleukin-6 and C-reactive protein in patients with benign and malignant prostate disease

Abstract: The relationship between interleukin-6 and C-reactive protein was evaluated in patients with benign (n ¼ 59) and malignant (n ¼ 86) prostate disease. The correlation coefficients for patients with benign prostatic disease and prostate cancer were r s ¼ 0.632, Po0.001 and r s ¼ 0.663, Po0.001, respectively. These results indicate that the relationship between interleukin-6 and C-reactive protein is similar in patients with benign and malignant prostate disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 19 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…Similarly, inflammation may play a role in PCa development (23). Indeed, inflammatory markers such as C-reactive protein (CRP) and Il-6 have been linked with both CAD progression and poorer PCa outcomes (24,25). Unfortunately, CRP levels or any other marker of systemic inflammation were not available in the current study.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, inflammation may play a role in PCa development (23). Indeed, inflammatory markers such as C-reactive protein (CRP) and Il-6 have been linked with both CAD progression and poorer PCa outcomes (24,25). Unfortunately, CRP levels or any other marker of systemic inflammation were not available in the current study.…”
Section: Discussionmentioning
confidence: 67%
“…It is of interest therefore that McArdle et al (2004b) have recently reported that the relationship between interleukin-6 and C-reactive protein was similar in benign prostatic hyperplasia and prostate cancer, and that there was no relationship between interleukin-6 and PSA concentrations. This would suggest that, in prostate cancer at least, interleukin-6 is produced by the inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that interleukin-6, which is largely responsible for the production of CRP [9][10][11] , can be produced by prostatic tumours [12] . Furthermore, increased circulating concentrations of interleukin-6 have been shown to be associated with reduced survival in patients with prostate cancer [13] .…”
Section: Discussionmentioning
confidence: 99%